Chromosome-level genome assembly of Fistularia commersonii (Syngnathiformes, Fistulariidae) - Zufa Ding; Cheng Wang; Yuting Qian; Wenjun Chen; Dan Yu; Yang Liu; Liandong Yang; Ying Wang (Scientific Data)
Abstract The bluespotted cornetfish (Fistularia commersonii), a Lessepsian sprinter species, is distributed in the inter-tropical zone across the entire Indo-Pacific, ranging from the Tropical Eastern Pacific to the Red Sea. In this study, we achieve assembly of a chromosome-level genome for F. commersonii by harnessing the precision of PacBio HiFi sequencing in conjunction with the sophistication of Hi-C sequencing technologies. The assembly yields a size of 638.75 Mb, achieving a distribution rate of 99.35% across 36 chromosomes. Notably, the contig N50 value stands at 15.67 Mb, while the scaffold N50 value reaches an impressive 18.69 Mb. BUSCO analysis demonstrates a genome completeness of 96.9% for F. commersonii. Repetitive elements constitute approximately 29.61% of the genome’s size. A total of 20,961 protein-coding genes are predicted, with 95.97% of them having functional annotations. This high-quality assembly provides crucial resources for future studies on the invasion mechanisms of F. commersonii, as well as for comparative genomics research on seahorses and pipefish.